α-Mangostin Induces Apoptosis and Inhibits Metastasis of Breast Cancer Cells via Regulating RXRα-AKT Signaling Pathway - Zhu, Xiuzhi; Li, Jialin; Ning, Huiting; Yuan, Zhidong; Zhong, Yue; Wu, Suzhen; Zeng, Jin-Zhang (Frontiers in Pharmacology, 2021)
Mangostin, which has the function of anti-inflammatory, antioxidant, and anticancer, etc, is one of the main active ingredients of the hull of the mangosteen. The main objective of the study was to elucidate its anti-cancer function and possible mechanism. α-Mangostin was separated and structurally confirmed. MTT method was used to check the effect of mangostin on breast cancer cell proliferation. Then the effect of α-Mangostin on the transcriptional activity of RXRα was tested by dual-luciferase reporter gene assay. And Western blot (WB) was used to detect the expression of apoptosis-related proteins or cell cycle-associated proteins after treatment. Also, this study was to observe the effects of α-Mangostin on the invasion of breast cancer cell line MDA-MB-231. α-Mangostin regulates the downstream effectors of the PI3K/AKT signaling pathway by degrading RXRα/tRXRα. α-Mangostin can trigger PARP cleavage and induce apoptosis, which may be related to the induction of upregulated BAX expression and downregulation of BAD and cleaved caspase-3 expression in MDA-MB-231 cells through blockade of AKT signaling. The experiments verify that α-Mangostin have evident inhibition effects of invasion and metastasis of MDA-MB-231 cells. Cyclin D1 was involved in the anticancer effects of α-Mangostin on the cell cycle in MDA-MB-231 cells. α-Mangostin induces apoptosis, suppresses the migration and invasion of breast cancer cells through the PI3K/AKT signaling pathway by targeting RXRα, and cyclin D1 has involved in this process.